Tamm Review: Shifting global fire regimes: Lessons from reburns and research needs - Prichard, Susan J.; Stevens-Rumann, Camille S.; Hessburg, Paul F. (Forest ecology and management, 2017)
•We reviewed published studies on reburns in fire-adapted ecosystems of the world.•Fire regimes often have shifted from frequent to infrequent fire return intervals.•Legacies of past burns constrain the spread and severity of future fires.•Periodic fire generally favors fire-adapted vegetation and limits closed forests.•Better understanding of reburns informs climate change adaptation methods. Across the globe, rising temperatures and altered precipitation patterns have caused persistent regional droughts, lengthened fire seasons, and increased the number of weather-driven extreme fire events. Because wildfires currently impact an increasing proportion of the total area burned, land managers need to better understand reburns – in which previously burned areas can modify the patterns and severity of subsequent fires. For example, knowing how long past fire boundaries can function as barriers to fire spread may empower decision-makers to manage some wildfires as large-scale fuel treatments, or alternatively, determine where prescribed burning or strategic wildfire management are required. Additionally, a clear understanding of how prior burn mosaics influence future fire spread and burn severity is critical knowledge for landscape and fire-dependent wildlife habitat planning under a rapidly changing climate. Here, we review published studies on reburns in fire-adapted ecosystems of the world, including temperate forests of North America, semi-arid forests and rangelands, tropical and subtropical forests, grasslands and savannas, and Mediterranean ecosystems. To date, research on reburns is unevenly distributed across the world with a relative abundance of literature in Australia, Europe and North America and a scarcity of studies in Africa, Asia and South America. This review highlights the complex role of repeated fires in modifying vegetation and fuels, and patterns of subsequent wildfires. In fire-prone ecosystems, the return of fire is inevitable, and legacies of past fires, or their absence, often dictate the characteristics of subsequent fires.